Além do lugar comum : imagens clichês, fabulações poéticas e geografias menores em Terra Vermelha-ES - Santos, Maria da Penha dos (2013)
The certainty of the existence of various possibilities of presenting a place, the purpose of this work is the search for ways to express other geographical ways of thinking the being in the world. From the photographic language and poetry, our proposal is to deterritorialise the hegemonic visual discourse, using the minor literature, from the perspective of Deleuze and Guattari. In our study, we focused on the “Grande Terra Vermelha” region, in Vila Velha City/ES”. This region is presented as a place where, since its origin, has been highlighted as violent due to the large number of murders committed in the region. Based on post-structuralist presuppositions, this experiment intends to show that there are other possible versions, especially those that occur through the poetic fables. In other words, the idea is to promote a representation beyond the commonplace, deterritorializing and blurring the standard image.